Analisis Perawatan Mesin Kiln Dry Menggunakan Metode Preventive Maintenance - Ariq Maulana; Cahyo Prasojo; Ahmad Rois Fathul In’am; Muhammad Alanatha Musyafa; Sukarno Budi Utomo (Journal of Engineering and Applied Technology, 2026)
This study evaluates the operational reliability and thermal efficiency of a conventional kiln dry installation through a longitudinal action research approach. By investigating six critical mechanical subsystems, the research maps component degradation patterns under maximum load conditions using the functional matrix of heating, circulation, ventilation, control, structure, and safety modules. Empirical data from real-time checklists, infrared thermography inspections, and maintenance logs were validated using triangulation techniques to analyze schedule compliance, mechanical downtime durations, and early anomaly detection indices. The findings indicate that higher maintenance schedule compliance directly correlates with reduced mechanical downtime and stable micro-climate control within the drying chamber. Furthermore, a critical cause-and-effect analysis reveals that external spare part lead times significantly accelerate component aging and cause substantial lifetime deviations from manufacturer specifications. Consequently, micro-climate instability induces severe geometric defects, internal checking, and structural collapse in the timber pores. Implementing a structured, pro-active preventive maintenance policy effectively mitigates operational bottlenecks, guarantees phytosanitary treatment standards, and systematically improves the overall output quality of industrial wood manufacturing.